Від релігії до націоналізму: трансформація єврейської ідентичності - Бен-Рафаель, Е. (Народна творчість та етнографія, 2008)
All in all, nationalisms draw on the religious background of the population, even where the nationalists reject it personally. This perspective sheds light on Jewish nationalism, since the religion-people link has always been aprimary code of Judaism. It is against this background that we focus here on the question of collective identity. The Jewish case of national identity illustrates, in this respect, a case where nationalism integrates basic principles of action vis-a-vis the world and society, by disembodying them from the religious cosmogony and setting them in a new perspective with new meanings. Once a part of the national identity, such principles take on meanings that accord with, and support the establishment of a nation-state. The transformation necessitates drastic changes in the attitudes of individuals vis-a-vis their experience and environment, but which, at the same time, presents itself as the culmination of the collective's destiny. It is in this perspective that one may understand the transformation of the Jewish religious identity into ingredients of various formulations of the national Jewish identity.